The effects of catalyst composition on the catalytic production of dimethyl carbonate - Chin, CS; Shin, D; Won, G; Ryu, J; Kim, HS; Lee, BG (ELSEVIER, 2000)
The synthesis of dimethyl carbonate (DMC) by oxidative carbonylation of MeOH has been studied in the presence of various catalyst systems. The effect of catalyst composition on the catalytic activity and product composition is investigated. A three-component catalyst system composed of PdCl2(PPh3)(2), Cu(OMe)(2) and Me4NCl shows synergy effects in terms of the MeOH conversion (26%) and DMC selectivity (95%). The reaction performed in the presence of a single-component catalyst PdCl2(PPh3)(2) produces dimethoxy methane (DMM) as a major product with selectivity over 90%, while the addition of Me4NCl or Cu(OMe)(2) to PdCl2(PPh3)(2) results in the increase of DMC selectivity from 2% to 60%. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: OXIDATIVE CARBONYLATION; ELECTROLYTIC CARBONYLATION; GAS-PHASE; METHANOL; MECHANISM; METHOXIDE; COMPLEXES; DIOXIDE; BASE; CO